Transcriptome Analyses in BV2 Microglial Cells Following Treatment With Amino-Terminal Fragments of Apolipoprotein E - Pollock, Tanner B.; Cholico, Giovan N.; Isho, Noail F.; Day, Ryan J.; Suresh, Tarun; Stewart, Erica S.; McCarthy, Madyson M.; Rohn, Troy T. (Frontiers in Aging Neuroscience, 2020)
Despite the fact that harboring the apolipoprotein E4 (APOE4) allele represents the single greatest risk factor for late-onset Alzheimer’s disease (AD), the exact mechanism by which ApoE4 contributes to disease progression remains unknown. Recently, we demonstrated that a 151 amino-terminal fragment of ApoE4 (nApoE41-151) localizes within the nucleus of microglia in the human AD brain and traffics to the nucleus causing toxicity in BV2 microglia cells. In the present study, we examined in detail what genes may be affected following treatment by nApoE41-151. Transcriptome analyses in BV2 microglial cells following sublethal treatment with nApoE41-151 revealed the upregulation of almost 4,000 genes, with 20 of these genes upregulated 182- to 715-fold compared to untreated control cells. The majority of these 20 genes play a role in the immune response and polarization towards microglial M1 activation. As a control, an identical nApoE31-151 fragment that differed by a single amino acid at position 112 (CysArg) was tested and produced a similar albeit lower level of upregulation of an identical set of genes. In this manner, enriched pathways upregulated by nApoE31-151 and nApoE41-151 following exogenous treatment included Toll receptor signaling, chemokine/cytokine signaling and apoptosis signaling. There were unique genes differentially expressed by at least 2-fold for either fragment. For nApoE31-151, these included 16 times as many genes, many of which are involved in physiological functions within microglia. For nApoE41-151, on the other hand the number genes uniquely upregulated was significantly lower, with many of the top upregulated genes having unknown functions. Taken together, our results suggest that while nApoE31-151 may serve a more physiological role in microglia, nApoE41-151 may activate genes that contribute to disease inflammation associated with AD. These data support the hypothesis that the link between harboring the APOE4 allele and dementia risk could be enhanced inflammation through activation of microglia.